Low testosterone level increases fasting blood glucose level in adult males - Suweino Suweino; ML Eddy Parwanto; David Tjahjadi (Faculty of Medicine, Universitas Trisakti, 2012)
BACKGROUND Total testosterone (TT) levels in males decrease with age. There has been a vigorous debate on the extent to which low testosterone causally contributes to diabetes and its complications. The aim of the present study was to determine the relationship between sex hormones and blood glucose levels in adult males. METHODS A cross-sectional study involving 259 males aged 41 - 70 years was conducted at Cilandak Subdistrict, South Jakarta. Sex hormone binding globulin (SHBG) and testosterone levels were measured by means of electro–chemiluminescent immunoassay (ECLIA), while blood glucose levels were measured enzymatically using a spectrophotometer. Free testosterone index (FTI) and body massa index (BMI) were calculated. Inter-variable relationships were tested by Pearson correlation analysis, followed by multiple linear regression analysis to determine the most influential factor on fasting blood glucose levels. RESULTS BMI was positively correlated with fasting blood glucose, but the correlation was statistically not significant (r=0.105; p=0.106). In contrast, total testosterone (TT) (r=-0.258; p=0.000) and SHBG (r=-0.193; p=0.02) had a significant negative correlation with fasting blood glucose level. Multiple linear regression showed that TT was the most influential factor on fasting blood glucose level (â=-0.044; p=0.008). CONCLUSIONS Low total testosterone level may increase fasting blood glucose level in adult males. SHBG levels did not predict fasting blood glucose levels.Assessment of testosterone in middle-aged men may allow early intervention for diabetes mellitus.